Exploring N-Back Cognitive Training for Children With ADHD - Jones, Masha R. (J Atten Disord, 2018)
The efficacy of n-back training for children with Attention Deficit Hyperactivity Disorder (ADHD) was tested in a randomized controlled trial. Forty-one children aged 7–14 with ADHD trained on an n-back task, and their performance was compared with that of an active control group (n = 39) who trained on a general knowledge and vocabulary task. The experimental group demonstrated transfer of training to a non-trained n-back task as well as to a measure of inhibitory control. These effects were correlated with the magnitude of training gains. Our results suggest that n-back training may be useful in addressing some of the cognitive and behavioral issues associated with ADHD.